Network Analysis Shows Novel Molecular Mechanisms of Action for Copper-Based Chemotherapy - Espinal-Enríquez, Jesús; Hernández-Lemus, Enrique; Mejía, Carmen; Ruiz-Azuara, Lena (Frontiers in Physiology, 2016)
The understanding of the mechanisms associated with the action of chemotherapeutic agents is fundamental to assess and account for possible side-effects of such treatments. Casiope\'inas have demonstrated a cytotoxic effect by activation of pro-apoptotic processes in malignant cells. Such processes have been proved to activate the apoptotic intrinsic route, as well as cell cycle arrest. Despite this knowledge, the whole mechanism of action of Casiope\'inas is yet to be completely understood. In this work, we implement a systems biology approach based on two pathway analysis tools (Over-Representation Analysis and Causal Network Analysis), to observe changes in some hallmarks of cancer, induced by this copper-based chemotherapeutic agent in HeLa cell lines. We find that the metabolism of metal ions is exacerbated, as well as cell division processes being globally diminished. We also show that cellular migration and proliferation events are decreased. Moreover, the molecular mechanisms of liver protection are increased in the cell cultures under the actions of Casiope\'inas, unlike the case in many other cytotoxic drugs. We argue that this chemotherapeutic agent may be promising, given its protective hepatic function, concomitant with its cytotoxic participation in the onset of apoptotic processes in malignant cells.